Efeito das enzimas recombinantes de Schistosoma mansoni Hipoxantina-Guanina Fosforibosiltransferase (HGPRT) e Purina Nucleosídeo Fosforilase (PNP) no tratamento da esquistossomose experimental - Fragelli, Bruna Dias de Lima (Universidade Federal de São Carlos, 2018)
Schistosomiasis is a disease that affects a large number of people in 78 countries. The number of cases has increased in recent years and there is no vaccine and new drugs, a worrying aspect, since there is loss of sensitivity to the drug used, Praziquantel. The present study aimed to evaluate the effects of the recombinant enzymes of S. mansoni Hypoxanthine-Guanine Phosphoribosyltransferase (HGPRT) and Purine Nucleoside Phosphorylase (PNP) and the MIX of the two enzymes in the treatment of schistosomiasis in the murine model. Female mice of the Balb / c strain were infected with cercariae and treated intraperitoneally with 3 doses of 100 μg of the proteins at 10 day intervals from the 28th day of infection. Egg numbers were counted in the feces on the 48th and 54th days after infection by the Kato-Katz method. On the 55th day after infection, adult worms were retaken from the hepatic and mesenteric intestinal system, global and differential counts of LCP and blood cells. Cytokines IFN-γ, IL-4 and IL-10 in plasma were also quantified, as well as the production of antibodies of the IgG2a and IgE classes. For the analysis of the granulomas and deposition of collagen histological laminae of the liver were made. Our results demonstrate that treatment with the HGPRT enzyme appears to stimulate the production of IL-4 and IL-10 cytokines and promoted significant reduction of liver granulomas in infected and treated animals. Treatment with the PNP enzyme was able to reduce the number of worms in the liver and in the mesenteric vessels of the intestine. The PNP and MIX enzyme treatment were able to reduce the number of eggs in the faeces and negatively modulate the number of eosinophils in the PCL and in the blood. Therefore, treatment with the recombinant enzymes of S. mansoni HGPRT and PNP seems to contribute to the control and reduction of pathophysiological aspects of schistosomiasis, contributing to the reduction of morbidity associated with schistosomiasis in the murine model.
Keywords: Imunoterapia; Hipoxantina-Guanina Fosforibosiltransferase (HGPRT); Purina Nucleosil Fosforilase (PNP); Immunotherapy; Hypoxanthine-Guanine Phosphoribosyltransferase (HGPRT); Purine Nucleosil Phosphorylase (PNP); CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::IMUNOLOGIA; CIENCIAS BIOLOGICAS::PARASITOLOGIA